Variações espaço-sazonais da qualidade da água e da hidrodinâmica em ecossistemas aquáticos sob aspectos ambientais no Baixo Rio Jari-AP - ABREU, Carlos Henrique Medeiros de (Universidade Federal do Amapá, 2020)
The objective of this research is to present a 'state of the art "on water quality in the basin of river Jari-AP, considering the importance of the hydrologic cycle and the context of use and occupation of the land. The research focuses on the environmental impact assessment (EIA) of the hydroelectric plant of Santo Antonio do Jari (UHESAJ), in the period between 2005-2014. The methodology applied is the review of techno-scientific contributions of literature, divided into two basic steps: ) summary review of water resources, limnology, public health and environmental risks in the Jari River basin; b) interpretation and analysis of physical, chemical and biological parameters of water quality and their space-seasonal variations, considering the hydrological context. The results indicated that some economic enterprises and disorderly urban occupation in the Jari-AP River basin tend to negatively influence the quality of water, as well as in most of the cases reported in EIA studies in Brazil, whose changes in the patterns of water quality are already significant and detected by monitoring in its lower course. We conclude that, close to urban, industrial and installation of UHESAJ, there is the most environmentally threatened stretch, with significant effect on water quality, highlighting color, phosphorus, fecal coliform (TC) and Escherichia coli parameters. This research is a contribution to future studies of water quality in the basin, which usefulness is to serve as support for new research and management of aquatic ecosystems, normally no available literature in the Amazon